2020
DOI: 10.1111/hel.12696
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori test‐and‐treat strategy for second‐year junior high school students aimed at the prevention of gastric cancer in Takatsuki City

Abstract: BackgroundMore than 90% of gastric cancer cases are caused by Helicobacter pylori infections. To prevent gastric cancer, an H pylori test‐and‐treat strategy targeting young people has been implemented in various places in Japan. In this study, we evaluated the effectiveness of an H pylori test‐and‐treat strategy for second‐year junior high school students in Takatsuki City.Materials and MethodsIn 2014‐2017, a urine‐based H pylori test was used for initial screening. The final infection status was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Thus, it can be considered that the eradication of H. pylori infection in younger generation is beneficial, and recent studies indicated the successful eradication of H. pylori using eradication protocols for adult; however, detailed information regarding the adverse reactions was not included in the study 9–11 . Recently, several studies in Japan have performed H. pylori eradication therapy in junior high school students to prevent the further carcinogenesis of H. pylori infection, including our previous studies 7,12–14 . These studies have clearly indicated adverse reactions related to the eradication therapy in children.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, it can be considered that the eradication of H. pylori infection in younger generation is beneficial, and recent studies indicated the successful eradication of H. pylori using eradication protocols for adult; however, detailed information regarding the adverse reactions was not included in the study 9–11 . Recently, several studies in Japan have performed H. pylori eradication therapy in junior high school students to prevent the further carcinogenesis of H. pylori infection, including our previous studies 7,12–14 . These studies have clearly indicated adverse reactions related to the eradication therapy in children.…”
Section: Introductionmentioning
confidence: 97%
“…However, these were not serious adverse events. The safety of eradication therapy of H. pylori with triple therapy containing vonoprazan fumarate for adolescents remains unclear; however, reports have shown no major problems in short-term evaluations 9,12,16 . In the present study, the number of cases was limited, and only adverse events during oral administration of antibacterial drugs and P-CAB were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, triple therapy with proton-pump inhibitor (PPI), amoxicillin, and clarithromycin is an effective first-line treatment for H. pylori infection in children 13 . In Japan, potassium-competitive acid blocker (P-CAB) may be used instead of PPI in adults 7,14,15 , and P-CAB may be used because of high frequency of CAM-resistance H. pylori, even in adolescents 9,12,16 . To date, H. pylori eradication therapy has no serious side effects in children 9,12,16,17 ; however, there is a need to conduct a long-term evaluation.…”
mentioning
confidence: 99%
“…Considering that the current infection route of H. pylori is person-to-person transmission, particularly within the same family [1], [8], young individuals must take measures against H. pylori infection from the viewpoint of preventing this infection in the next-generation. Based on such circumstances, as a new method of preventing gastric cancer, the screening and treatment of H. pylori infection among young individuals have begun as a primary prevention in Japan [9], [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, triple therapy with potassium-competitive acid blocker (P-CAB), amoxicillin, and clarithromycin is an effective rst-line treatment for H. pylori infection in adults [13,14] and children [9,12]. To date, H. pylori eradication therapy has no serious side effects in children [9], [15].…”
Section: Introductionmentioning
confidence: 99%